Process optimization and kinetic study for commercialization of UHLA process. (April 2019) - Biswas, Pinakpani; Sarkar, Santanu; Sarkar, Supriya
Abstract: The prime objective of the present study is to establish the Ultra High Lime Alumina (UHLA) process for desalination of clarified water at commercial scale whereas, very limited information is available for such purpose. This process was used for removal of chloride from coke quenching water having high salinity. The process parameters were optimized with help of the Design of Experiment. As the kinetics of UHLA process plays a major role in deducing proper sizing of stirred tank reactor, a model has developed with help of non-linear optimization technique for evaluation of kinetics parameters using the data obtained from pilot plant study. The process followed second order reaction kinetics with 80% chloride removal efficiency. A detailed analysis and characterization of input water, treated water and solid waste were conducted that would help us to access the further utilization of solid material generated in UHLA process. The process feasibility has been established for commercialization of the present process in steel industry perspective.